RNA sequencing of intestinal mucosa reveals novel pathways functionally linked to celiac disease pathogenesis - Leonard, Maureen M.; Bai, Yu; Serena, Gloria; Nickerson, Kourtney P.; Camhi, Stephanie; Sturgeon, Craig; Yan, Shu; Fiorentino, Maria R.; Katz, Aubrey; Nath, Barbara; Richter, James; Sleeman, Matthew; et al. (PloS one, 2019)
The early steps in the pathophysiology of celiac disease (CD) leading to loss of tolerance to gluten are poorly described. Our aim was to use RNA sequencing of duodenal biopsies in patients with active CD, CD in remission, and non-CD controls to gain insight into CD pathophysiology, identify additional genetic signatures linked to CD, and possibly uncover targets for future therapeutic agents. We performed whole transcriptome shotgun sequencing of intestinal biopsies in subjects with active and remission CD and non-CD controls. We also performed functional pathway analysis of differentially expressed genes to identify statistically significant pathways that are up or down regulated in subjects with active CD compared to remission CD. We identified the upregulation of novel genes including IL12R, ITGAM and IGSF4 involved in the immune response machinery and cell adhesion process in the mucosa of subjects with active CD compared to those in remission. We identified a unique signature of genes, related to innate immunity, perturbed exclusively in CD irrespective of disease status. Finally, we highlight novel pathways of interest that may contribute to the early steps of CD pathogenesis and its comorbidities such as the spliceosome, pathways related to the innate immune response, and pathways related to autoimmunity. Our study confirmed previous findings based on GWAS and immunological studies pertinent to CD pathogenesis and describes novel genes and pathways that with further validation may be found to contribute to the early steps in the pathogenesis of CD, ongoing inflammation, and comorbidities associated with CD.